Purchasing and supply management W. C. Benton, Jr. - Benton, Jr., W. C. (New York McGraw - Hill/Irwin, 2007)
The author outlines the most current methods in purchasing and supply chain management. With his step-by-step approach, both students and professionals can gain analytical purchasing skills. Real case studies and exercises help students transform purchasing theory into purchasing practice and implementation. Some of the topics include purchasing business processes, price cost analysis, professional services, and transportation, global, and healthcare purchasing.
Includes bibliographical references and index
Keywords: Quản trị kinh doanh